KNOWLEDGE, ATTITUDE, AND BEHAVIORS TOWARD ANTIBIOTICS OF NON-MEDICAL STUDENTS JOUF UNIVERSITY, SAUDI ARABIA - Mostafa-hedeab, Gomaa (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to investigate the knowledge and attitude of non-medical students, Jouf University toward antibiotic. Methods: Data were collected from male and female students using a self-prepared questionnaire then tabulated and analyzed using SPSS program. Results: This study included 1035 students; 573 (55.3%) male and 462 (44.6%) female, aged (21.5Â±2.2) years. About 533 (51.5%) used antibiotic during the year 2015. 705 (68.12%) of the student display wrong answer regarding the uses of the antibiotic. 53.5% depending on the previous prescription on self-medicated antibiotic (SAM), followed by their experience (14.5%) and pharmacy advice (11.3%). 45.9% did not have any idea about the antibiotic name they used. Majority of the students (62.6%) stop antibiotic once improvement is achieved, whereas (28.1%) complete the course till the end of the last dose. 75.4% of the studied populations saving at least one antibiotic at home while 62.7% sharing antibiotic with others. 35.3% of the studied population did not experienced antibiotic-related side effects, while 19.3% experience nausea. About 57.6% believed that broad spectrum is better than narrow-spectrum antibiotic, 70.4% deny that higher doses enhance recovery, (57.3%) believes that low dose decrease side effect. 51.9% depend on their good medical knowledge for SMA, while 20.3% was to save time, 18.8% dependent on pharmacy expert where only 9% was to save money cost. Conclusion: The majority of the sample had a fair level of knowledge in relation to antibiotics. Initiation of national program and campaigns toward antibiotic uses to raise the public awareness about the hazardous of antibiotic misuse/abuse is essential to decrease the gap between antibiotic use and attitude.